PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SINAR BANJARAN ABADI - Anggi Haerani; Rohaelis Nuraisiah (Jurnal Manajemen dan Bisnis, 2020)
This study aimed to investigate and analyze the influence of motivation and discipline to employee performance at PT Sinar Banjaran Abadi. The method used is path analysis (path analisys), because this research in addition to want to get an overview of the performance of employees associated with the motivation and discipline of work, also get an idea of the pattern of the relationship and the influence of variable- variable research that has been set. Based on the research results can be that the motivation of the employees at PT SIBA at a low level towards good enough, then owned by employees working discipline in a low position towards good enough. In general, motivation and discipline affect the performance of employees at PT SIBA, and motivation is the most significant influence on employee performance. The effect of partially variable motivation on employee performance of 50.36%, variable discipline to employee performance amounted to 24.50%.Simultaneously influence the motivation and discipline to employee performance amounted to 74.86%, while 25.1% is influenced by other variables that tida examined in this study.From the research that is done, then the variable motivation and discipline when combined will have a significant effect on the performance of employees at PT Sinar Abadi Banjara (SIBA).